Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10050956
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome and Molecular Analyses Reveal Significant Karyotype Diversity and Provide New Evidence on the Origin of Aegilops columnaris

Abstract: Aegilops columnaris Zhuk. is tetraploid grass species (2n = 4x = 28, UcUcXcXc) closely related to Ae. neglecta and growing in Western Asia and a western part of the Fertile Crescent. Genetic diversity of Ae. columnaris was assessed using C-banding, FISH, nuclear and chloroplast (cp) DNA analyses, and gliadin electrophoresis. Cytogenetically Ae. columnaris was subdivided into two groups, C-I and C-II, showing different karyotype structure, C-banding, and FISH patterns. C-I group was more similar to Ae. neglecta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…While in F 2 , the chromosome pair 4R4R only supplemented the wheat chromosome set [69], in F 5 , 4R4R was added to wheat chromosomes in 58.59% of plants and replaced chromosomes of the fourth homeologous group in 13.15% of plants, which implies its compensational and competitive activity in a new genomic environment. The short arm of chromosome 4R is known to be homeologous to wheat chromosome arms 4BS and 4DS, and partially homeologous to chromosome arm 4AL [109], which is itself involved in evolutionary translocations between chromosome arms 4AL, 5AL, and 7BS [37,39]. On the other hand, it has been shown that rye chromosomes are incorporated into the wheat genome at different frequencies depending on cross direction and genotype [110,111].…”
Section: Chromosome Instability In F 5 1rv(1a) × R Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in F 2 , the chromosome pair 4R4R only supplemented the wheat chromosome set [69], in F 5 , 4R4R was added to wheat chromosomes in 58.59% of plants and replaced chromosomes of the fourth homeologous group in 13.15% of plants, which implies its compensational and competitive activity in a new genomic environment. The short arm of chromosome 4R is known to be homeologous to wheat chromosome arms 4BS and 4DS, and partially homeologous to chromosome arm 4AL [109], which is itself involved in evolutionary translocations between chromosome arms 4AL, 5AL, and 7BS [37,39]. On the other hand, it has been shown that rye chromosomes are incorporated into the wheat genome at different frequencies depending on cross direction and genotype [110,111].…”
Section: Chromosome Instability In F 5 1rv(1a) × R Hybridsmentioning
confidence: 99%
“…Intra-and interspecific divergence, accompanied by species-specific chromosome rearrangements, have been found in two wheat groups, Emmer and Timopheevii [36]. Although all extant wild wheat have x = 7, comparative cytogenetics highlights considerable chromosomal rearrangements within and among wild diploid and polyploid species [37][38][39].…”
Section: Introductionmentioning
confidence: 99%